(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article provides information on the description, classification, use in chemical treatment against harmful organisms, as well as ensuring the safety of sprayers used in agriculture in the Republic of Uzbekistan for the environment and humans.